Post Traumatic Stress Disorder among Critical Illness Survivors: A Pragmatic Review of Literature - Skariah Koshy; Molly John; Roy K. George; Ligi Rachel Daniel (Indian Journal of Psychiatric Nursing)
Enhancements in critical care medicine have contributed to improve functional status and increased rates of patient survival. Consequently, studies have concentrated on long-term effects, such as the mental health effects of critical illness and the quality of life among critical illness survivors. This systematic review examines the prevalence of post traumatic stress disorder (PTSD) among critical illness survivors and identifies risk factors contributing to its development. A comprehensive search was performed in PubMed database for studies published from 2013 to 2023. The inclusion criteria include observational (cohort, cross-sectional, and case–control) studies that address prevalence of PTSD in adult critical illness survivors aged ≥18 years and admitted for at least 24 h in intensive care unit (ICU). Studies were reviewed using Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Each individual study was assessed for methodological quality and risk bias using Joanna Briggs Institute critical appraisal checklist for studies reporting prevalence data. Twenty-eight studies met the inclusion criteria, where findings revealed substantial variation in the prevalence of PTSD between 0.3% and 46.1%. Risk factors for post-ICU PTSD can be categorized into two groups: those related to the actual ICU experiences and nonmodifiable pre-ICU characteristics (including age, gender, and history of depression). Survivors of critical illness are at increased risk for PTSD, highlighting the need for targeted psychological interventions. Understanding the prevalence and its contributing factors of PTSD among critical illness survivors provides valuable insights into their distress.